2005
DOI: 10.1037/0012-1649.41.1.193
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Problem Behavior Status to Children's Negative Emotionality, Effortful Control, and Impulsivity: Concurrent Relations and Prediction of Change.

Abstract: The relations of children's internalizing and externalizing problem behaviors to their concurrent regulation, impulsivity (reactive undercontrol), anger, sadness, and fearfulness and these aspects of functioning 2 years prior were examined. Parents and teachers completed measures of children's (N = 185; ages 6 through 9 years) adjustment, negative emotionality, regulation, and behavior control; behavioral measures of regulation also were obtained. In general, both internalizing and externalizing problems were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
392
6
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 383 publications
(450 citation statements)
references
References 68 publications
32
392
6
15
Order By: Relevance
“…When the children were age 4.5 to just turning 8 years of age, children with borderline or clinical level externalizing problems (comorbid or not), in comparison to nondisordered children, were low in attention focusing, attention shifting, and inhibitory control, and high in impulsivity. This same pattern of findings was obtained two years later (Eisenberg et al, 2005). At the first assessment, children with pure (not co-morbid) internalizing problems, in comparison to nondisordered children, were low in attentional effortful control and impulsivity, but did not differ in inhibitory control.…”
Section: The Relations Of Anger Effortful Control and Reactive Undesupporting
confidence: 63%
See 3 more Smart Citations
“…When the children were age 4.5 to just turning 8 years of age, children with borderline or clinical level externalizing problems (comorbid or not), in comparison to nondisordered children, were low in attention focusing, attention shifting, and inhibitory control, and high in impulsivity. This same pattern of findings was obtained two years later (Eisenberg et al, 2005). At the first assessment, children with pure (not co-morbid) internalizing problems, in comparison to nondisordered children, were low in attentional effortful control and impulsivity, but did not differ in inhibitory control.…”
Section: The Relations Of Anger Effortful Control and Reactive Undesupporting
confidence: 63%
“…In United States, the relation of internalizing problems with anger was weak in early elementary school and increased with age into middle elementary school; thus, we were unsure if anger would relate to internalizing problems. We also were unsure about the relations of adjustment with attentional control because they were evident at a mean age of 6 but not 8 years in the United States (Eisenberg et al, 2005). As in the United States, relatively high attentional and inhibitory effortful control, low anger, and moderate impulsivity were expected to predict nondisordered status.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, when children are low in effortful control, they are likely to exhibit negative outbursts, to behave inappropriately with peers and adults, and to behave aggressively. Consistent with these expectations, researchers have found that low effortful control is associated with and predicts behavior problems in preschool and school-aged populations Eisenberg et al, 2005;Eisenberg, Spinrad, et al, 2004;Kochanska & Knaack, 2003;Olson, Sameroff, Kerr, Lopez, & Wellman, 2005). Although the majority of work has been done with older children, Kochanska and Knaack (2003) found negative relations between effortful control at ages 22, 33, and 45 months and later externalizing problems at 73 months.…”
mentioning
confidence: 92%